Improving surgical learning and performance at unicompartmental knee arthroplasty - Alvand, A (2014)
Surgery is a difficult skill to teach and even more difficult to assess. In the context of orthopaedic surgery, the Oxford unicompartmental knee arthroplasty (OUKA) is a commonly performed and technically challenging procedure with a variable and sometimes unsatisfactory revision rate. Thus there is a need to develop methods for optimising performance in this procedure. This thesis aims to use this procedure to explore ways of improving teaching methods and assessment methods, and the use of novel technologies to impact surgical performance. No validated technical skill assessment system currently exists to evaluate surgical performance during OUKA. A consensus-based framework of expert opinion (Delphi methodology) was therefore used to determine the essential technical steps of OUKA to aid development of a technical skill assessment system. A procedure-specific assessment scale named the Oxford Arthroplasty Technical Skill Score (OATSS) was produced. Two clinical studies were conducted to demonstrate the inter-rater reliability and construct validity of OATSS in the real operating theatre. This is the first time that a procedure-specific assessment scale has been developed and validated for a complex orthopaedic procedure. The Delphi methodology was also used to identify important radiographic parameters that could be used to predict clinical outcome following OUKA. Two cohort studies used post-operative radiographs of "failed" and "poorly functioning" OUKA cases (with matched controls) to identify several radiographic parameters that can predict the increased risk of a poor clinical outcome. A virtual reality (VR) based simulator (called ViTAL) was developed to teach the cognitive skills necessary for performing the OUKA procedure. This software-based learning environment was used in a randomised controlled study to assess its training effectiveness. This demonstrated that, when used alongside existing teaching modalities, ViTAL resulted in better acquisition of cognitive skills in novice trainees. A randomised controlled study was subsequently undertaken using anatomic dry-model bones in a surgical skills laboratory to determine the effect of cognitive skills training using the ViTAL simulator on the ability of orthopaedic trainees to perform the OUKA procedure. The previously validated OATSS assessment scale was used to evaluate surgical performance. Results demonstrated that this type of training not only improved acquisition of cognitive skills, but also resulted in better technical skill performance during OUKA procedures. This demonstrates, for the first time, the effectiveness of a purely cognitive VR-based simulator for improving technical skills during arthroplasty surgery. Patient-specific instrumentation (PSI) is a novel and exciting technological development within orthopaedic surgery. A prospective RCT was performed to compare OUKAs implanted using PSI with those implanted using conventional instrumentation. Intra-operative measurements, together with post-operative radiographic analyses, were performed to determine the accuracy of component positioning. With regards to positioning of the femoral component, there was no difference between the accuracy of PSI and conventional instrumentation. However, accuracy of PSI was poor with regards to positioning of the tibial component. Further improvement to the PSI is needed before this can be recommended for routine use. In conclusion, this thesis has demonstrated that improvement of learning and assessment methods is currently the safest and most feasible means of optimising surgical performance during the OUKA procedure. Although it is important to embrace novel training modalities and technological developments in an attempt to enhance surgical performance, they must be scientifically evaluated to ensure that they deliver real clinical improvements.